2016
DOI: 10.18287/jbpe16.02.010303
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo investigation of glycerol diffusion in skin tissue

Abstract: Abstract. The change of optical parameters of rat skin ex vivo under the action of aqueous 30%, 50%, 60%, 70%, 85%, and 100% glycerol solutions has been experimentally studied. The analysis of kinetics of the change of the studied parameters has allowed the estimate of the diffusion coefficient dependence upon the concentration of glycerol in the skin and the efficiency of optical clearing for each of the glycerol solutions. The results can find application in the development of new methods of noninvasive diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 18 publications
(37 reference statements)
3
22
0
Order By: Relevance
“…Strongly bound water, which is approximately 44% of the total water in the skin (0‐200 μm), can also take part in this flux, but at lower mobility. These results are in good agreement with the results presented in and are slightly lower that the result obtained for muscle tissues . This difference can be explained by the skin heterogeneity and different water bounding properties of epidermis and dermis in comparison with other tissues.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Strongly bound water, which is approximately 44% of the total water in the skin (0‐200 μm), can also take part in this flux, but at lower mobility. These results are in good agreement with the results presented in and are slightly lower that the result obtained for muscle tissues . This difference can be explained by the skin heterogeneity and different water bounding properties of epidermis and dermis in comparison with other tissues.…”
Section: Resultssupporting
confidence: 91%
“…Only for that condition, glycerol or iohexol molecules are flowing. Thus, it was shown that 60% to 70% glycerol solution has the lowest diffusion coefficient in skin because only glycerol molecules are involved in diffusion process . In our case, weakly bound water and unbound water (together approximately 55% of total water in the skin [0‐200 μm]), as most mobile water types, are mostly included in the water flux in the skin during the OC process.…”
Section: Resultsmentioning
confidence: 63%
“…In stratum corneum, the D values for water are in the order of 10 −11 − 10 −9 cm 2 /s . For white laboratory rats, glycerol molecules have D ≅ 10 −6 cm 2 /s in ex vivo skin (dermis) and glucose and ethylene glycol (EG) have D ≅ 10 −7 cm 2 /s in ex vivo muscle , one order lower than for water in the same tissues . Similar values have been obtained for glycerol ( D ≅ 10 −7 cm 2 /s) and water ( D ≅ 10 −6 cm 2 /s) in human liver and for glucose ( D ≅ 10 −7 cm 2 /s) and water ( D ≅ 10 −6 cm 2 /s) in normal and pathological colorectal mucosa .…”
Section: Introductionsupporting
confidence: 54%
“…Glycerol solutions of different concentrations are frequently used for optical clearing of tissues [11,[14][15][16]. Our choice of concentration for the glycerol solution was determined by its relatively low viscosity (22.5 cP) in comparison with the dehydrated glycerol (1410.0 cP) [17] and yet sufficiently high refractive index of 1.427 [17] (Table 1).…”
Section: J Of Biomedical Photonics and Eng 3(2)mentioning
confidence: 99%
“…Our choice of concentration for the glycerol solution was determined by its relatively low viscosity (22.5 cP) in comparison with the dehydrated glycerol (1410.0 cP) [17] and yet sufficiently high refractive index of 1.427 [17] (Table 1). Moreover, the studies of the efficiency of skin optical clearing using aqueous glycerol solutions of different concentrations [11,14,16] have shown that the concentration of 70% is close to optimal. Table 1 Refractive index and viscosity of glycerol solutions of different concentration [17].…”
Section: J Of Biomedical Photonics and Eng 3(2)mentioning
confidence: 99%